Investigating the Application of Islamic Economic Law in Modern Economics: A Qualitative Study on the Concepts of Riba and Zakat - Elsa Maya Sari; Ewa Gustianda; M. Reivaldy Elfitra (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
This research investigates the application of Islamic Economic Law (IEL) within the context of modern economics, focusing on the fundamental concepts of riba (usury) and zakat (almsgiving). Utilizing a qualitative method, the study analyzes the principles of Islamic economics as derived from the Quran and Hadith. It also examines the interpretation and application of these concepts in the economic practices of Muslim communities. Through a descriptive approach, the research aims to identify and elucidate the phenomenon related to Islamic Economic Law in depth. The findings reveal that IEL is a comprehensive legal framework based on Islamic teachings, including the Quran, Sunnah, and the results of Ijtihad (independent reasoning). Fundamental principles of IEL highlighted in the study include justice, honesty, and balance, which are essential in all economic activities. This research contributes to a deeper understanding of how Islamic principles can be integrated into modern economic systems, promoting ethical and equitable economic practices.